Harmonization of civil legislation in the field of protection of ownership rights to real estate objects in contractual obligations through the transfer of the buyer’s rights and obligations in the case of the sale of a share in a joint partial ownership with the law of the European Union - Hnativ, Oksana (Actual problems of law (Aktual’ni problemi pravoznavstva), 2023)
The article investigates the protection of property rights to real estate objects in contractual obligations by transferring the rights and obligations of the buyer in the event of the sale of a share in a joint partial ownership through the lens of European legislation. Proposals and innovations concerning improvement of property rights protection for real estate objects are submitted by transferring the rights and obligations of the buyer in the event of the sale of a share in joint ownership in contractual obligations.